Nitric Oxide Is a Mediator of Antiproliferative Effects Induced by Proinflammatory Cytokines on Pancreatic Beta Cells - Laura Quintana-Lopez; Manuel Blandino-Rosano; Gonzalo Perez-Arana; Alberto Cebada-Aleu; Alfonso Lechuga-Sancho; Manuel Aguilar-Diosdado; Carmen Segundo (Mediators of Inflammation)
Nitric oxide (NO) is involved in several biological processes. In type 1 diabetes mellitus (T1DM), proinflammatory cytokines activate an inducible isoform of NOS (iNOS) in β cells, thus increasing NO levels and inducing apoptosis. The aim of the current study is to determine the role of NO (1) in the antiproliferative effect of proinflammatory cytokines IL-1β, IFN-γ, and TNF-α on cultured islet β cells and (2) during the insulitis stage prior to diabetes onset using the Biobreeding (BB) rat strain as T1DM model. Our results indicate that NO donors exert an antiproliferative effect on β cell obtained from cultured pancreatic islets, similar to that induced by proinflammatory cytokines. This cytokine-induced antiproliferative effect can be reversed by L-NMMA, a general NOS inhibitor, and is independent of guanylate cyclase pathway. Assays using NOS isoform specific inhibitors suggest that the NO implicated in the antiproliferative effect of proinflammatory cytokines is produced by inducible NOS, although not in an exclusive way. In BB rats, early treatment with L-NMMA improves the initial stage of insulitis. We conclude that NO is an important mediator of antiproliferative effect induced by proinflammatory cytokines on cultured β cell and is implicated in β-cell proliferation impairment observed early from initial stage of insulitis.